For whom we forgive matters: relationship focus magnifies, but self‐focus buffers against the negative effects of forgiving an exploitative partner. (22nd November 2017) - Gabriels, Jordan Brian; Strelan, Peter
Abstract : Increasingly, studies indicate that victims experience negative outcomes after forgiving offenders who present an exploitation risk. However, we demonstrate that the link between exploitation risk and forgiveness‐related outcomes is dependent upon a victim's focus of forgiving. Two studies, the first employing a prospective design ( N = 110) and the second an experimental scenario method ( N = 261), replicate previous research on the negative effects of exploitation risk and also test two new hypotheses. First, we found that forgiving explicitly for the sake of a relationship is associated with greater distress, relative to deciding to forgive for the sake of the self. Second, we found that relationship‐focussed forgiveness magnified the distress caused by exploitation risk, whereas self‐focussed forgiveness, relative to relationship‐focussed forgiveness, provides a buffer against it. In short, these findings demonstrate that for whom we forgive matters. We discuss theoretical and practical implications for understanding when forgiving is costly.